IMPLEMENTATION OF BLUE ECONOMY AS AN ALTERNATIVE FOR SUSTAINABLE DEVELOPMENT FINANCING - Beni Hartono; Giantoro Rudiman; Abet Alpha Pardede; Muammar Khaddafi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
Indonesia has marine potential spread over a sea area of 5.8 million square km consisting of a territorial area of 3.2 million square km and an Indonesian Exclusive Economic Zone (ZEEI) area of 2.7 million square km. Apart from that, Indonesia has the second longest coastline in the world, with a total length of 81,000 km. However, Indonesia's maritime economic development has not yet provided an optimal contribution to national prosperity and progress, to date the contribution of Indonesia's maritime gross domestic product (GDP) is in the range of 7%, which is still considered relatively small. Furthermore, looking at the 14th SDGs goal, namely Marine Ecosystems, in the marine ecosystem goals in this SDGs there is a policy that has been made by the Indonesian government, namely in 2020-2024 which contains improving maritime and marine management, improving fisheries governance, and revitalization. sustainable fishing practices. To fulfill funding for the seven development agendas stated in the 2020-2024 RPJMN, funding of USD 1,641.3 billion is needed. Meanwhile, the State Revenue and Expenditure Budget (APBN) is only able to fund around 20-25 percent of these needs, including the needs of the maritime, fisheries and maritime sectors. Sustainable infrastructure financing has an important role in achieving Sustainable Development Goals (SDGs), especially those related to conservation and preservation of marine resources. In an effort to overcome financing challenges, Blue Finance emerged as a promising solution. By using financing instruments such as blue bonds/Sukuk and the Government Cooperation Scheme with Business Entities (KPBU), Blue Finance has the potential to attract private participation and specifically support marine elementary school conservation or preservation projects and programs.